Biomass and metabolism of zooplankton in the Bransfield Strait (Antarctic Peninsula) during austral spring - Hernández-León, S.; Torres Curbelo, Santiago; Gomez, M; Montero, I.; Almeida, C. (Polar Biology, 1999)
Zooplankton biomass (as dry weight), respiration and ammonia excretion were studied in three different size classes (200–500, 500–1000 and >1000 μm) in the Bransfield Strait during December 1991. Average mesozooplankton biomass was 86.45 ± 56.74 mg · dry weight · m−2, which is in the lower range of the values cited in the literature for polar waters. Higher biomass was observed in the Weddell water. The small size fraction accounted for about 50% of total biomass while the largest one represented 35%. Rather high metabolic rates were found, irrespective of whether the organisms were incubated in the presence of food. No significant differences were observed in mass specific respiration and ammonia excretion rates between different temperatures of incubation (0.2–2.3°C) and between the size classes studied. Because of the very low biomass values observed, the metabolic requirements of mesozooplankton during December represented a small fraction of the primary production.